Human extraocular muscles in mitochondrial diseases: comparing chronic progressive external ophthalmoplegia with Leber’s hereditary optic neuropathy - Carta, A (Copyright 2005 British Journal of Ophthalmology, 2005)
Aims: To compare the ultrastructural aspects of human extraocular muscles in two types of mitochondrial disease: chronic progressive external ophthalmoplegia (CPEO) and Leber’s hereditary optic neuropathy (LHON). Methods: Muscle samples of the medial rectus obtained from surgery in a sporadic case of CPEO associated with deleted mitochondrial DNA, and post mortem in a case of 3460/ND1 LHON were processed for electron microscopy (EM). The medial rectus from an autoptic time to fixation matched control was used to exclude postmortem artefacts. Results: The CPEO specimen revealed focal areas of disruption and abnormalities of mitochondria in some muscle fibres, creating a “mosaic-like” pattern. In the LHON specimen a diffuse increase in both number and size of mitochondria (mean diameter 0.85 μm v 0.65 μm of control, p<0.0001) with swollen appearance and disorganised cristae filled all spaces of sarcoplasmic reticulum. In some areas the excessive number of mitochondria slightly distorted myofibrils. Conclusion: EM investigation of extraocular muscles in CPEO and LHON reveals marked differences. A “mosaic-like” pattern caused by a selective damage of muscle fibres was evident in CPEO, whereas a diffuse increase in mitochondria with preservation of myofibrils characterised the LHON case. These ultrastructural changes may relate to the different expression of the two diseases, resulting in ophthalmoplegia in CPEO and normal eye movements in LHON.